Motherhood in the American Woman Poetâ€™s Perspective: A Short Glance at Allenâ€™s Rock Me to Sleep - Kurnia, Nandy Intan (Bina Nusantara University, 2015)
Article scrutinized one of the works of an American woman poet named Elizabeth Akers Allen. The poem underÂ study entitled â€œRock Me to Sleepâ€. It was a portrayal of motherhood. The speaker of this poem is a woman who is longingÂ for the love of her mother. She is seeking for a way to ease her pain since she feels that she has lost her own battle ofÂ womanhood. Although the mother remains absent, the readers of the poem can sense the powerful love of the speaker ofÂ the poem toward her mother. Method of this study was library research that carried out by applying descriptive analyticalÂ methods. Data were collected from the primary and secondary sources. Results of this paper are the writer of poetryÂ wants to warn people that womanhood in the patriarchal society can create many problems, and the only remedy for thoseÂ problems is motherhood. Article also proves that a writer does not have to be a feminist to produce a literary text whichÂ discusses the issue of women, which has became the focus of feminism.